2004
DOI: 10.1596/1813-9450-3431
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development, Financial Fragility, and Growth

Abstract: This paper studies the apparent contradiction between two strands of the literature on the effects of financial intermediation on economic activity. On the one hand, the empirical growth literature finds a positive effect of financial depth as measured by, for instance, private domestic credit and liquid liabilities (e.g., . On the other hand, the banking and currency crisis literature finds that monetary aggregates, such as domestic credit, are among the best predictors of crises and their related economic do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
296
3
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(336 citation statements)
references
References 46 publications
33
296
3
4
Order By: Relevance
“…Short-term heterogeneity in the growth processes between countries would not come as a surprise to many economic historians, but the problem has also attracted considerable attention in the more recent literature. Recent applications of the mean group and pooled mean group estimators in the growth context include Lee et al (1998), Bassanini and Scarpetta (2002), Loayza and Ranciere (2006) as well as Tan (2009). In our context, pooled mean group estimation carries an additional advantage as it enables us to distinguish between short-run and long-run effects of tariff protection.…”
Section: Pooled Mean Group Estimationmentioning
confidence: 98%
“…Short-term heterogeneity in the growth processes between countries would not come as a surprise to many economic historians, but the problem has also attracted considerable attention in the more recent literature. Recent applications of the mean group and pooled mean group estimators in the growth context include Lee et al (1998), Bassanini and Scarpetta (2002), Loayza and Ranciere (2006) as well as Tan (2009). In our context, pooled mean group estimation carries an additional advantage as it enables us to distinguish between short-run and long-run effects of tariff protection.…”
Section: Pooled Mean Group Estimationmentioning
confidence: 98%
“…To investigate the finance and growth relationship, Loayza and Ranciere (2006) and Demetriades and Law (2006) adopted the Pooled Mean Group (PMG) estimators proposed by Pesaran, Yongcheol, and Ron (1999) with its advantage of controlling for country heterogeneity in the financeegrowth nexus. Using a sample of 75 countries and annual data for the period from 1960 to 2000 and based on the PMG estimator, Loayza and Ranciere (2006) found that while financial intermediation had a positive and significant effect on economic growth in the long run, this effect was significantly negative in the short run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kaminsky and Reinhart (1999) found that channels of financial development have plausible negative effect on economic development by triggering instabilities in financial sector. Because of financial instabilities, a positive long-run relationship exist among output and financial intermediation, whereas in short-run the relationship becomes negative (Loayza & Ranciere, 2006). Rousseau and Wachtel (2011) explain that irrespective of country's stage of development, a positive impact of financial growth get weakens with the passage of time.…”
Section: Review Of Literaturementioning
confidence: 99%